2014
DOI: 10.1001/jama.2014.2850
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Use of Ambulance-Based Thrombolysis on Time to Thrombolysis in Acute Ischemic Stroke

Abstract: clinicaltrials.gov Identifier: NCT01382862.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
353
1
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(370 citation statements)
references
References 23 publications
4
353
1
8
Order By: Relevance
“…The Prehospital Acute Neurological Treatment and Optimization of Medical care in Stroke Study (PHANTOM-S) in Germany reported their MSTU significantly decreased stroke alert-to-treatment times from 76 minutes to 52 minutes, and significantly increased thrombolysis rates from 21% to 33% with no increase in the risk of intracerebral hemorrhage. 15 Among patients receiving thrombolytic therapy, the same German group also reported the proportion of so-called "golden-hour thrombolysis" was 6-fold higher with MSTU deployment.…”
Section: Mobile Stroke Treatment Unitsmentioning
confidence: 97%
“…The Prehospital Acute Neurological Treatment and Optimization of Medical care in Stroke Study (PHANTOM-S) in Germany reported their MSTU significantly decreased stroke alert-to-treatment times from 76 minutes to 52 minutes, and significantly increased thrombolysis rates from 21% to 33% with no increase in the risk of intracerebral hemorrhage. 15 Among patients receiving thrombolytic therapy, the same German group also reported the proportion of so-called "golden-hour thrombolysis" was 6-fold higher with MSTU deployment.…”
Section: Mobile Stroke Treatment Unitsmentioning
confidence: 97%
“…The Prehospital Acute Neurological Treatment and Optimization of Medical Care in Stroke Study showed that the time from notification to treatment was reduced by 25 minutes and the rate of thrombolysis increased by 12% in patients treated by an MSU when compared with standard EMS care. 10 The study also did not report any increases in adverse effects due to tPA administration when compared with traditional treatment. Another controlled study in Saarland, Germany, showed that the use of MSUs allowed a reduction of 41 minutes in the median time needed to make a therapeutic decision from alarm to therapy (35 minutes with MSU vs 76 minutes with regular care).…”
Section: Mobile Stroke Unitsmentioning
confidence: 85%
“…4,10,15,16,29,35,37,41,44 The greatest delay in the treatment of stroke patients has been shown to be in the prehospital phase, in which the patient is transported to a stroke specialty facility. 21 In an effort to combat this delay, the concept of the MSU was developed.…”
Section: Mobile Stroke Unitsmentioning
confidence: 99%
“…Pilotstudier med CT-utstyrt hjerneslagambulanse har vaert gjennomført i Tyskland (Ebinger, Winter & Wendt, 2014 ten. I Alta er det også naturlig at en CT-maskin lokaliseres ved legevakten.…”
Section: Status Og Utfordringerunclassified